Methemoglobinemia and Delayed Encephalopathy After 5-Bromo-2-Nitropyridine Poisoning: A Rare Case Report - Longke Shi; Longke Shi; Guangcai Yu; Liwen Zhao; Liwen Zhao; Zixin Wen; Zixin Wen; Yaqian Li; Baotian Kan; Baotian Kan; Xiangdong Jian; Xiangdong Jian (Frontiers Media S.A., 2022)
5-bromo-2-nitropyridine, an intermediate in the synthesis of pharmaceutical and pesticide products, is toxic to the human body. However, 5-bromo-2-nitropyridine poisoning has not been previously reported. Here, we report the case of a 40-year-old man who suffered skin and respiratory tract exposure to leaked 5-Bromo-2-nitropyridine at work. After exposure, the patient rapidly developed dizziness, fatigue, nausea, vomiting, chest distress, diffuse cyanosis, and coma. Methemoglobinemia, hemolytic anemia, rhabdomyolysis, and acute renal failure were observed after admission. He improved markedly after treatment, but delayed encephalopathy was confirmed 82 days after the exposure. This case highlights that 5-bromo-2-nitropyridine can be absorbed through the skin and respiratory tract, resulting in methemoglobinemia and delayed encephalopathy.